An Overview of Prescription in the Nursing - Ghofrani Kelishami, Fatemeh; Gholamnezhad, Haniyeh; Abbaszadeh, Abbas; Rasoolzadeh, Nasrin (Advances in Nursing & Midwifery, 2020)
Introduction: The role which nurses are playing in medication management is seriously changing over time. Nurses are authorized to prescribe medications in an ever-increasing number of countries. The main objective of the present review study is to introduce nurse prescribing as well as different types of prescriptions and their corresponding advantages, disadvantages, and barriers in the leading countries of nursing. Methods: The present study was performed by searching over the articles in information databases such as “PubMed”, “Google Scholar”, “Embase” , “Proquest”, “Ovid”, “Web of Science” and “Science Direct” using the English keywords such as “independent prescribing”, “supplementary nurse prescribing” and “prescribing”. As a result, 250 relevant papers were collected, out of which 38 ones were used in the present study. Results: The results of searching the sources and articles related to nurse prescribing were presented as the definition of nurse prescribing as well as different types of prescribing and their advantages and obstacles in the leading countries in nurse medication prescribing. Conclusions: Although there are many advantages for nurse prescribing such as cost-effectiveness of this method, the official prescribing by nurses is not authorized in many Asian countries such as Iran. Considering the positive role of nurse prescribing in the nursing professional improvement and the patient's satisfaction, it is also hoped to be applied in all countries.